Protective and therapeutic effects of Pilose antler against kidney deficiency-induced osteoporosis - Ren, Cong; Gong, Wei; Li, Feng; Xie, Ming (Cellular and Molecular Biology, 2019)
This study was carried out to evaluate the preventive and curative effects of Pilose antler against osteoporosis due to kidney deficiency, and investigate its potential mechanism of action. A model of osteoporosis due to kidney deficiency was established in rats using bilateral ovariectomy. Pilose antler polypeptide (PAP), Pilose antler polysaccharide (PAP'), and their mixture (PAP+PAP') were separately administered to the rats for 12 weeks, with progynova and xianlingubao tablets (XLGB) as the positive control groups. We determined the bone mineral density (BMD) and uterus Index of the rats. Osteoblastic bone metabolism-related indices in serum and bone tissue were measured with ELISA. Western blotting and RT-PCR were used to investigate the protein and mRNA expressions of Bmp-2, Smad1, Smad5, Runx2 in bone tissue. The morphology of bone tissue was determined using immunohistochemical methods. Compared with control group, PAP, PAP', PAP+PAP' increased BMD and regulated bone metabolism indices in serum and bone tissue. Treatment with Pilose antler up-regulated the mNRA and protein expressions of Bmp-2, Smad1, Smad5 and Runx2. Immunohistochemical staining showed that Bmp-2, Smad1, Smad5 and Runx2 were stained brown, indicating that all of them were positive. There were abnormal changes in the protein expressions of Bmp-2, Smad1, Smad5 and Runx2 in bone tissue, which may be an important mechanism underlying the development of kidney deficiency osteoporosis. Moreover, PAP, PAP' and PAP+PAP' had some preventive effects on osteoporosis, probably via the activation of the Bmp-2/Smad1 and Smad5/Runx2 signaling pathways through induction of high expressions of their mRNAs and proteins.